2016
DOI: 10.5502/ijw.v6i1.487
|View full text |Cite
|
Sign up to set email alerts
|

The development and longitudinal evaluation of a wellbeing programme: An organisation case study

Abstract: Abstract:Wellbeing programmes are often initiated in organisations based on an assumption that they will promote employee engagement and performance. But the specific elements of a wellbeing programme are rarely evaluated for their efficacy. This case study reports on the development and refinement of a wellbeing programme at a large multi-site European organisation, analysing the utility of wellbeing offerings and the impact of the programme on employee wellbeing over the course of five years. Results from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, organizations might have impact on employee wellbeing through a positive psychological climate of the organization and by enhancing employees' engagement (Shuck, & Reio, 2014) and therefore facilitating organizational performance (Shuck et al, 2011). A case study by Sutton et al (2016) also highlighted that an examined wellbeing program enhanced employee engagement. The approach is also supported by the research of Johnson et al (2020), concluding in that mindfulness training supports mental health, wellbeing and performance of employees.…”
Section: Organizational Impacts Of Employee Wellbeingmentioning
confidence: 99%
“…Moreover, organizations might have impact on employee wellbeing through a positive psychological climate of the organization and by enhancing employees' engagement (Shuck, & Reio, 2014) and therefore facilitating organizational performance (Shuck et al, 2011). A case study by Sutton et al (2016) also highlighted that an examined wellbeing program enhanced employee engagement. The approach is also supported by the research of Johnson et al (2020), concluding in that mindfulness training supports mental health, wellbeing and performance of employees.…”
Section: Organizational Impacts Of Employee Wellbeingmentioning
confidence: 99%
“…Indeed, some researchers suggest that various types of training (e.g., training on student mental health or professional development for teacher and student wellbeing) should be increased in schools (Schley et al, 2017;White & Kern, 2018), and research on teachers using JD-R theory also recognizes professional development and training as important resources for teacher wellbeing (Simbula et al, 2012). There is also evidence to suggest that organizational wellbeing training increases the wellbeing of employees (Sutton et al, 2016). In regard to our finding of changes in time, Castro et al (2010) found that a significant risk factor for teacher wellbeing was a heavy workload (paperwork, meetings, grading).…”
Section: Key Findings and Practical Implicationsmentioning
confidence: 99%
“…If you as a company leader plan to hold a meeting, then the meeting is so complicated to solve the problem, you had better invite employees who have subjective well-being and better happiness. According to Sutton, Evans, Davies, & Lawson (2016), subjective wellbeing has a positive impact on work.…”
Section: The Importance Of Subjective Well-beingmentioning
confidence: 99%